Emphasis of Eco-friendly concepts in the Secondary-level Science Curriculum of Sri Lanka - Mathura, U.; Piratheeban, K. (University of Colombo, 2023)
This mixed-method study was carried out to examine the emphasis on environmental concepts in the secondary-level science curriculum of Sri Lanka, compared with Singapore and India, considering the gender and grades. For the qualitative phase, primary resources were reviewed and for the quantitative phase, 285 students were selected (total population = 1078) through stratified random sampling. A questionnaire was adopted from Ugulu et al.(2013) and Kaiser et al. (1999) and categorized under three dimensions: Usage of non-biodegradable items (BioD), Eco-friendly attitude (EF) and Conservation of resources (CR) (α=0.749). Much importance is not given to direct environmental concepts in the curriculum of Sri Lanka with the insufficient number of periods allocated for environmental-related units(Grades 6-11: 11.2%, 15.4%, 0, 8.3%, 0 and 13.4% respectively). Additionally, most of the learning outcomes focus on acquiring knowledge rather than eco-friendly attitudinal change. Also, the emphasis given to environmental attitudinal change in the curriculum is identified at a low level compared with Singapore and India. Among the means of fifteen items, only the attitude of using reusable boxes instead of lunch sheets is very high (M = 4.34). Meanwhile, dimensions EF (M = 3.53) and CR (M = 3.70) are at a higher level than BioD (M=3.28). Furthermore, none of the dimensions (PBioD = 0.512, PEF = 0.732, PCR = 0.226) has a significant difference with gender. Also, it revealed that the grade influences eight attitudes out of fifteen selected attitudes. Therefore, this study concluded that students’ attitudes towards the environment are positive in general with dimension BioD needing more attention with no influence of gender over the environmental attitudes. In conclusion, more emphasis should be placed to environmental concepts in the existing science curriculum of Sri Lanka in order to make attitudinal changes in the students, resulting in an eco-friendly generation.
Keywords: Science curriculum; Environmental attitude; Biodegradable; Eco-friendly attitude; Conservation of resources